Prevalence of ciprofloxacin‐resistant Enterobacteriaceae in the intestinal flora of patients undergoing transrectal prostate biopsy in Norwich, UK. (25th March 2015) - Hanna, Marcelino Yazbek; Tremlett, Catherine; Josan, Gurvir; Eltom, Ali; Mills, Robert; Rochester, Mark; Livermore, David M.
<x xml:space="preserve">Abstract</x> Objective To determine the efficacy of fluoroquinolone prophylaxis in patients undergoing transrectal ultrasonography (TRUS)‐guided biopsy of the prostate in the Norwich population, and its correlation with ciprofloxacin resistance in the faecal flora. We also aimed to determine the usefulness of a pre‐biopsy rectal screen for resistant bacteria in these patients. Patients and Methods The incidence and microbiology of sepsis after TRUS‐guided prostate biopsies between 2007 and 2011 was audited retrospectively. Subsequently, in 2012, a prospective study was performed, collecting the same data but also culturing rectal swabs from all patients undergoing TRUS‐guided biopsy, with a post‐biopsy follow‐up period of 6 months. All patients were given prophylactic oral ciprofloxacin, as per Trust policy (750 mg 1 h before biopsy, followed by 250 mg twice daily for 3 subsequent days). Results Between 2007 and 2011, 3600 patients underwent TRUS‐guided biopsy. Among these, 11 (0.3%) were admitted to hospital for post‐biopsy related sepsis but only 4 (0.1%) had ciprofloxacin‐resistant Escherichia coli confirmed from blood cultures: three had ciprofloxacin‐susceptible Enterobacteriaceae, and four had no ciprofloxacin susceptibility data. In 2012, 10 (3.7%) of 267 patients sampled before biopsy had ciprofloxacin‐resistant E. coli recovered on rectal swab culture but none of these men presented with post‐biopsy sepsis; during the 6‐month follow‐up period, seven patients were diagnosed with urinary tract infections. Conclusion Ciprofloxacin‐resistant Enterobacteriaceae remains rare in the intestinal flora of the Norwich TRUS population, meaning that the drug remains adequate as prophylaxis. Pre‐biopsy rectal swabs may be useful for individual departments to periodically assess their own populations and to ensure their antibiotic policy remains valid. In populations where resistance is known to be highly prevalent, pre‐biopsy rectal swabs can help guide addition of further antibiotics to prevent post‐biopsy septicaemia.